PENGARUH DUKUNGAN SOSIAL TEMAN SEBAYATERHADAP MOTIVASI BELAJAR MAHASISWADIMODERASI OLEH KETERLIBATAN ORANG TUA - Silvi Regiana, - (2023)
This study aims to determine the effect of peer social support on student learning motivation moderated by parental involvement. The research involved 400 active students who still have their parents. Respondents filled out a learning motivation questionnaire compiled by Ibrahim (2020), a peer social support questionnaire compiled by Jundi (2017), and a parental involvement questionnaire compiled by Khalda (2022). The sampling technique used is accidental sampling. The data analysis technique used was multiple regression analysis and the Moderated Regression Analysis (MRA) technique with the help of the SPSS version 29 program. The results showed that parental involvement as a moderating variable from the influence of peer social support on learning motivation has a significance value of 0.192 (p>0.05). Based on these results, it can be concluded that the parental involvement variable does not moderate the effect of peer social support on student learning motivation. Keywords: Learning Motivation, Parental Involvement, Peer Social Support, Students